(untitled) (Docentes 2.0 Journal, 2022)
Since the declaration of a pandemic issued by the World Health Organization (WHO), the different contours in the daily life of human beings have been seriously altered. The main objective of the investigative inquiry process is to determine the quality of the skills, methods, and pedagogical support tools used by the teachers of the Economics program at the University of Pamplona. This research was developed under the analytical-synthetic method in the pragmatic paradigm with a mixed approach, exploratory type, and concurrent triangulation design. A sample group of 26 fourth, sixth, seventh, and eighth-semester students were abstracted from the population, and a digital questionnaire was sent to a sample group of 4 teachers. A survey was applied as instruments, analysis techniques, and data collection. The data is analyzed using the technique known as descriptive statistics, which is applied to the collected research and analyzes and characterizes a set of data. The study is relevant since it reveals the need to promote and develop digital skills in university teachers, ending the demands and trends of current education increasingly demand. Using digital tools and components as teaching support tools improves and transforms traditional teaching methods.